Susac syndrome: The effectiveness of Rituximab monotherapy - T. V. Beketova (Научно-практическая ревматология, 2023)
Susac syndrome (SS) or retino-cochleo-cerebral vasculopathy is an extremely rare, severe, and potentially disabling condition. Underlying occlusive microangiopathy in SS is clinically characterized by the triad of encephalopathy, sensorineural hearing loss and branch retinal arterial occlusion. SS therapy envisages simultaneous use of high doses of glucocorticoids, intravenous immunoglobulins, cyclophosphamide and rituximab (RTХ). This article presents a case of remitting-relapsing slow-progressive SS with typical clinical manifestations demonstrating successful treatment SS with RTХ monotherapy; it also discuss the focus of RTХ monotherapy should be targeted at SS cases with contraindications for glucocorticoids and cytostatics use, slow-progressive SS or at early stages.